Symptomatic upper extremity deep venous thrombosis after laser lead extraction - Maisary, Sameer al-; Kremer, Jamila; Romano, Gabriele; Karck, Matthias; De Simone, Raffaele (Brazilian journal of cardiovascular surgery, 2023)
INTRODUCTION: Laser lead extraction is a well-established method for removing unwanted leads with low morbidity and mortality. In this small series of cases, we documented our experience with venous thrombosis after laser lead extraction. METHODS: Retrospective data of patients who underwent laser lead extraction with postoperative axillo-subclavian vein thrombosis between May 2010 and January 2020 were analyzed. Demographic, operative, clinical, and follow-up characteristics of those patients were collected from our medical database. RESULTS: Six patients underwent percutaneous laser lead extraction. Mean age of the patients was 64±7 years. And four of them were male. A total of 11 leads with a mean age of 92±43.8 months were extracted. Patients presented with painful arm swelling postoperatively. CONCLUSION: Laser lead extraction may lead to symptomatic upper extremity deep venous occlusion.
Der Autor "Gabrielle Romano" heißt richtig: "Gabriele Romano"
Gesehen am 12.09.2023